ESSENCE AND FEATURES OF ECOLOGIZATION OF ECONOMY - A. S. Frolov (Вестник университета)
In the 21st century, economics and ecology have become even more closely interconnected and have a direct impact by each other than before. Ecologization of the economy is a focused process aimed at transforming economic activity by reducing the negative human impact on the environment. The article considers the causes, essence, main goals and principles of this process. As a result of the conducted research it was found out that the beginning of the concept of ecologization of economy is considered to be the second half of the XX century, when the world community began to pay special attention to the problems of negative impact of man on nature. In addition, the paper highlights the main characteristic features of this phenomenon, which include the orientation of economic activities towards rational use of natural resources and the transition to resource-saving sectors of the economy.